Numerical Study of Random Corrosion Characteristics of Metal Based On the Cellular Automata Method - Zekun, Zou; Guan, Wang; Linyuan, Kou; Qingrui, Yang; Pei, Zhang; Yiquan, Xu (International Journal of Integrated Engineering, 2022)
In the production process of coal chemical companies, the corrosion of metal equipment and the resulting shortening of its service life can cause safety hazards. Simulation modeling of pit emergence and development during corrosion evolution provides a new approach to corrosion research. By analyzing the effect of different parameters on causing corrosion to occur, it is possible to reflect the influence of complex physico-chemical systems. In this paper, the simulation of a meta-cellular automaton model of pit growth under diffusion and the introduction of a passivation probability to correct the chemical reaction rate are developed; The effect of reaction passivation probability, chemical reaction rate and diffusion coefficient on the degree of corrosion was also analyzed by means of quantitative analysis. The results show that for metal corrosion loss processes, the degree of corrosion damage decreases with increasing probability of reactive passivation and increases with increasing chemical reaction rate, increasing electrolyte concentration and increasing time step. The CA model was applied to simulate the growth and change of pitting corrosion of metal materials with their corrosion protection layer under damaged conditions. The corrosion model can simulate the corrosion morphology change characteristics similar to the real metal to the corrosion pit evolution simulation related research has certain scientific, validity, reference.